Pengaruh Subtitle pada Motion Graphics "Affordable" terhadap Pemahaman Siswa Kelas VII SMPN 7 Bogor - Ananda Prathama Saputra; Muhammad Hafidz Sidqi Riupassa; Amata Fami; Reneta Mega Zaskia (Jurnal Riset Rumpun Seni, Desain dan Media, 2024)
The aim of this study is to assess the influence of subtitles in the "Affordable" motion graphics on the comprehension of 7th-grade students at SMPN 7 Bogor. This research utilizes a quantitative descriptive approach. In this study, samples are obtained through non-probability sampling, and respondents are selected using purposive sampling. Simple linear regression is employed as the data analysis technique. The results of the simple linear regression analysis reveal that the "Affordable" motion graphics have a positive and significant impact on the comprehension of 7th-grade students at SMPN 7 Bogor, accounting for 24.46%, while the remaining 75.54% is influenced by other variables.